Perbaikan proses produksi dan ijin edar guna meningkatkan mutu produk unggulan daerah - Suprayogi Suprayogi; Nimas Mayang Sabrina Sunyoto; Mochammad Syamsul Hadi; Umi Fadhilah; Muthia El Afwa; Nadya Lulu Nur Aziza; Reni Zulismar; Bernardia Filia Nareswari; Izzati Ardhan Firdausyi (University of Islam Malang, 2021)
KWT